Counselling Utilization Experiences among Methadone Maintenance Treatment Clients in Rural and Small Urban Communities - Pickett, Nichole D.; Domene, José (Canadian Journal of Counselling and Psychotherapy, 2013)
As a result of growing rates of opiate dependence in Atlantic Canada, numerous methadone maintenance treatment (MMT) and associated counselling programs have been implemented. A qualitative study employed semistructured interviews to examine the counselling utilization experiences of 7 participants (4 males, 3 females) who were receiving MMT. Four salient themes were identified using an interpretive thematic analysis strategy, and results suggest that counselling was a beneficial supplement to methadone, but challenges existed with its implementation. Implications on how to improve the efficacy of available counselling are identified and discussed.